Platelet-derived growth factor in glioblastoma—driver or biomarker?. (November 2014) - Westermark, Bengt
Abstract The platelet-derived growth factor (PDGF) family of mitogens exerts vital functions during embryonal development, e.g. in the central nervous system, where PDGF drives the proliferation of oligodendrocyte precursors. PDGF and PDGF receptors are co-expressed in human glioblastoma (GBM). Whether an aberrant activation of the PDGF receptor pathway is a driving force in glioma development has remained an open question. In experimental animals, overexpression of PDGF has convincingly been shown to induce tumors, both in wild-type animals (marmoset, rat, mouse) and in mice with targeted deletions of suppressor genes, e.g. Tp53 or Ink4A. Targeting the PDGF receptor in tumor-bearing mice leads to growth inhibition and reversion of the transformed phenotype. Findings of PDGF receptor amplification or mutations in human GBM are strong indicators of a causative role of the PDGF receptor pathway. However, clinical trials using PDGF receptor antagonists have been disappointing. In conclusion, a PDGF receptor profile may be a biomarker for a subgroup of GBM originating from a PDGF receptor-responsive cell. Although compelling experimental and clinical evidence supports the notion that the PDGF receptor pathway is a driver in GBM, formal proof is still missing.